Pengaruh Inflasi, Bi Rate, Kurs Rupiah Dan Djia Terhadap IHSG Tahun 2014-2017 - Nugraha Ibnu Prayoga; Khairunnisa Khairunnisa (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
This study aims to determine how the influence of Inflation, BI Rate, Rupiah Exchange and Dow Jones Industrial Average on the Composite Stock Price Index listed on the Stock Exchange in 2014-2017. The population in this study is the Inflation, BI Rate, Rupiah and Dow Jones Industrial Average panel data in 2014-2017. The method of data analysis in this study is multiple linear regression using SPSS 25 software. Based on the results of data processing shows that, the Rupiah exchange rate has a positive and significant influence and the Dow Jones Industrial Average has a positive and significant effect. While Inflation and the BI Rate did not affect the ICI.